Socio-Economic Development of Transmigration Communities in Suka Damai Village, Singingi Hilir Sub-District, Kuantan Singingi District 1983-2020 - Elisah, Siti Nur; Bunari; Asyrul Fikri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Transmigration is one of the ways taken by the government to overcome population imbalances and equality caused by geographical, social, economic and political factors. Transmigration development is an integral part of national and regional development as an effort to accelerate development, especially in areas that are still isolated or underdeveloped, which can also improve the welfare of transmigrants and the surrounding community. The transmigration program for the Kuantan Singingi area began in 1980 with a focus on placement in the Sentajo Raya, Logas Tanah Darat, Singingi Hilir, and Singingi sub-districts, besides that seen from the data from 2000 to 2018 Singingi Hilir Sub-district experienced rapid development in terms of plantations, economy and infrastructure facilities when compared to the three sub-districts above. The research objectives are 1).To find out the background and process of transmigration in Suka Damai Village, Singingi Hilir District, Kuantan Singigi Regency. 2).To find out the socio-economic development of the transmigration community in Suka Damai Village, Singingi Hilir District, Kuantan Singingi Regency 1983-2020. 3). To find out the role of the government in encouraging the socio-economic development of the transmigration community in Suka Damai Village, Singingi Hilir District, Kuantan Singingi Regency 1983-2020. This research uses historical research methods. In its development, the socio-economy of the transmigration community has experienced better development. The socio-economic development of the transmigration community will not succeed without the role of the government. The Transmigration Office what was done in the early days of transmigration was to take care of all matters relating to transmigration, starting from the place, facilities, food and clothing, and all activities related to the community.